Introduction: Making Equality Count - RUSSELL, HELEN; MC GINNITY, FRANCES (The Liffey Press, 2010)
In spite of legislation outlawing discrimination across the EU, inequalities between groups appear to be an enduring feature of Irish and European societies. To what extent inequality is due to discrimination is a matter of continuing debate and controversy. Accurately measuring discrimination is therefore a crucial task, that is nonetheless very challenging. This has been a central task of a research programme on equality and discrimination carried out by the Economic and Social Research Institute and the Equality Authority, and was the theme of the conference `Making Equality Count? held in Dublin in June 2010.
Making Equality Count: Irish and International Research Measuring Equality and Discrimination
PUBLISHED
Keywords: Law; Equality legislation